Models of care for co‐morbid diabetes and chronic kidney disease. Issue 8 (29th July 2018) - Lo, Clement; Zimbudzi, Edward; Teede, Helena; Cass, Alan; Fulcher, Greg; Gallagher, Martin; Kerr, Peter G; Jan, Stephen; Johnson, Greg; Mathew, Tim; Polkinghorne, Kevan; Russell, Grant; et al.
Abstract: Diabetes and chronic kidney disease (CKD) are two of the most prevalent co‐morbid chronic diseases in Australia. The increasing complexity of multi‐morbidity, and current gaps in health‐care delivery for people with co‐morbid diabetes and CKD, emphasize the need for better models of care for this population. Previously, proposed published models of care for co‐morbid diabetes and CKD have not been co‐designed with stake‐holders or formally evaluated. Particular components of health‐care shown to be effective in this population are interventions that: are structured, intensive and multifaceted (treating diabetes and multiple cardiovascular risk factors); involve multiple medical disciplines; improve self‐management by the patient; and upskill primary health‐care. Here we present an integrated patient‐centred model of health‐care delivery incorporating these components and co‐designed with key stake‐holders including specialist health professionals, general practitioners and Diabetes and Kidney Health Australia. The development of the model of care was informed by focus groups of patients and health‐professionals; and semi‐structured interviews of care‐givers and health professionals. Other distinctives of this model of care are routine screening for psychological morbidity; patient‐support through a phone advice line; and focused primary health‐care support in the management of diabetes and CKD. Additionally, the model of care integrates with the patient‐centred health‐care home currently being rolled out by the Australian Department of Health. This model of care will be evaluated after implementation across two tertiary health services and their primary care catchment areas. Summary at a Glance: The review outlines the development of a model of care for patients with diabetes mellitus and chronic kidney disease, involving the multiple stake holders. Other distinctive features of this model of care are routine screening for psychological morbidity; patient‐support through a phone advice line; and focused primary health‐care support in the management of diabetes and CKD.